Efficacy of phosphonic acid applied by spraying and seed treatment at various concentrations for controlling downy mildew disease in maize - Ginting, Cipta; Pramesti, Elisa Amelia; Maryono, Tri; Sudarsono, Hamim; Susanto, Herry; Akin, Hasriadi Mat (Universitas Lampung, 2025)
Downy mildew, caused by Peronosclerospora spp., is one of the major problems in maize cultivation. Several studies have reported the development of resistance in Peronosclerospora spp. to metalaxyl, which had previously been an effective control method for the disease. Other research suggests that the efficacy of phosphonic acid in controlling downy mildew in maize is inconsistent. The objective of this study was to evaluate the efficacy of seed treatment with phosphonic acid in controlling downy mildew in Bisi 18 maize. The treatments were arranged in a randomized block design with six replications. The observed variables included the incidence and severity of the disease, the area under the disease progress curve (AUDPC), maize yield, and the content of tannin and hydroquinone compounds in maize leaves. The results showed that both phosphonic acid applied by spraying and seed treatment significantly reduced the incidence and severity of downy mildew (P < 0.05). However, the concentrations of phosphonic acid used in seed treatment had no significant effect on the disease during 1–7 weeks after inoculation. Furthermore, all phosphonic acid treatments tended to increase the content of tannin and hydroquinone compounds in maize leaves, which should be confirm quantitatively.